ASUHAN KEPERAWATAN DENGAN GANGGUAN INTEGRITAS KULIT PADA LANSIA PENDERITA DIABETES DI RUANG SANKAI RS NISHIHARA KEIAIEN JEPANG - Bahari, Egin Wahyu Septiawan; Kurniawan, Wasis Eko; Maryoto, Madyo (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2025)
Diabetes mellitus (DM) is a heterogeneous group of disorders characterised by elevated blood glucose levels or hyperglycaemia. Diabetes can cause ulcers, especially on the feet. Diabetic ulcers are open wounds that often occur in people with diabetes due to nerve and blood vessel damage caused by uncontrolled high blood sugar levels. These wounds can cause infection and, if left untreated, can lead to amputation. Wound ulcer treatment with NaCl (sodium chloride) or saline is a commonly used procedure to clean and keep the wound moist. NaCl 0.9% (intravenous fluid) is considered safe and effective because its composition is similar to blood plasma, so it does not cause irritation or allergic reactions. The design used in this case study research is descriptive research. The study in this research is a way to describe the application of nursing care in the elderly with skin integrity (back abscess) in the Sankai Room of RS Keiaien Okinawa Japan including assessment, diagnosis, intervention, implementation, and evaluation carried out on 11-13 June 2023. The subject of this case study is patient Mrs S with a medical diagnosis of DM in the Nikai room of Nishihara Keiaien Okinawa Hospital, Japan. The author conducted this research by interviewing and observing the case study subject to find information to compile a report conducted for 3x24 hours. The results of the final evaluation of the implementation of back abscess treatment with wound cleansing with NaCl 0.9% and the results of skin/tissue integrity disorders improved. Characterised by clients saying pain but has decreased, the wound looks dry, no need for dressings.